Pengakuan Terhadap Wilayah Baru Akibat Akresi Menurut Hukum Internasional - Waas, Armelia Febriyanty; Aksa, Lanang Dwi (Faculty of Law, Universitas Pattimura, 2024)
Introduction: In general, the territory of a country already existed when the country was born, because territory is one of the mandatory requirements for an entity to be called a country. However, in acquiring a territory, not all countries obtain the same route, there are several ways of obtaining a territory based on International Law. One of them is addition (accretion).Purposes of the Research: This research aims to describe and analyze claims regarding the phenomenon of the emergence of new areas due to natural accretion according to international law.Methods of the Research: The research method used in this writing is a normative legal research method, including research on legal principles, research on legal systematics, and international rules regarding claims to new territories that have emerged as a result of accretion. The data collected was analyzed qualitatively to provide an in-depth understanding of Recognition in international law and provide insight into a State's claim to a new territory due to natural accretion which prioritizes international rules regarding the conditions for claiming a new territory based on territorial boundaries. a State relating to State sovereignty.Results of the Research: The research results show that confession is a method of accepting factual situations which are then followed by legal consequences. The effect of granting recognition to the country that is given recognition is that it makes it easier for that country to carry out international transactions in the future. So, if another country has given recognition to the new country, this statement will automatically show that the new country has the same legal rights and obligations in international law. Apart from that, recognition is the acceptance of another country as a legal subject for another country to have the capacity and act as a legal subject. Recognition of new territory as a result of accretion must also be reviewed based on international law, which applies rules regarding the application of the boundaries of a country's territory to be able to claim the new territory.